Effect of Chloral Hydrate on Methane and Propionic Acid in the Rumen - Nevel, C. J. Van (1969)
Methane production from pyruvate by mixed rumen bacteria in vitro was nearly totally inhibited by chloral hydrate (0.1 μmole/ml of incubation fluid). This effect was accompanied by an accumulation of gaseous hydrogen and an increase in propionic acid production. Infusion of chloral hydrate (4 g/day) into the rumen of a sheep produced the same effects. Evidence is presented for a direct toxic effect of chloral hydrate upon methane bacteria. Results are discussed in terms of fermentation balances.